Experimental study of ammonia as an alternative fuel for modern spark Ignited internal combustion engines - Geng, Sikai (2024)
Innovations in spark-ignited internal combustion engines have been driven by soaring demands for increased efficiency and improved urban air quality. A critical step towards decarbonisation is the use of future low-carbon (neutral) fuels produced via renewable energy. Carbon-neutral energy carriers have attracted considerable attention as a means of controlling global greenhouse gas emissions. In spite of hydrogen being a highly attractive sustainable fuel, it continues to face fundamental challenges with storage and transportation processes which impede mass adoption. In very recent years, there has therefore been increasing interest in ammonia as an energy carrier, which is also a more effective carrier of hydrogen than liquid hydrogen on a volumetric basis. Key benefits include the ability to produce ammonia in a cost-effective manner at very large scale and relative ease and low cost of long-term storage. However, due to relative toxicity, future usage seems likely to be restricted to applications where industrial health and safety protocols can always be maintained.